(untitled) (Sains Humanika, 2011)
Reformation of Technical and Vocational Education (TVE) system becomes a priority that serve as an alternative to adapt the globalization changes in the most developing countries. Rapid changes of industrial and technology also give a significant impact towards TVE systems in Malaysia. Restructuring process of the education system show various changes and new paradigm has been implemented mainly for TVE in this country. However, to formulate a meaningful transformation process for TVE system, priority should be given to the development of framework plan to ensure an effective reformation process. The contents of the plan should not only fulfill intellectual need but also be able to unite the appreciation of knowledge, faith and practice in the process of developing human full potential. Malaysia’s approach of using the Western system in the process of formulating a strategic planning and education curriculum especially for Technical and Vocational education should be reviewed to ensure the implementation is properly resemblance with the important concepts emphasized in National Philosophy of Education. Based on the need to the realization of universal TVE, this article suggested the Technical and Vocational Education Strategic Transformation Plan (TVESTP) framework built with an emphasis on the integration of two major thrusts, namely spiritual and intellectual. Hopefully, the TVESTP framework will serve as the main reference for TVE transformation process and also in realizing the vision and mission of education which is to achieve self-actualization (human being with sense of slave only to God and as Godâ€™s khalifah; leader in social and career development) as the fundamental requirement in developing and producing a balance individual through TVE. Four main phases of TVESTP implementation method integrated with both of the thrusts also discussed generally troughtout this article.